Prevalence and Associated Factors of Lupus in the United States: Third National Health and Nutritional Examination Survey (NHANES III) - Leng, Xiaomei; Xia, Jin; Zeng, Xiaofeng; Song, Yiqing (Frontiers in Medicine, 2020)
This study aimed to examine the prevalence and associated factors of lupus among adults in the United States. This study included 20,045 participants aged 17 years and older from the Third National Health and Nutritional Examination Survey (NHANES III) from 1988 to 1994.Their lupus status was determined by survey questions in terms of a clinician’s diagnosis. Demographics and laboratory test results of all participants were collected, including biochemistry, nutrition, and antibody biomarkers. Continuous variables were compared between cases with reported lupus and non-case controls by t-test, while the Chi-square test was used for categorical variables. Weighted multivariate-adjusted logistic regression models after adjustment of covariates were used to identify associated factors of lupus risk. Of 20,045 participants, 40 people who self-reported a lupus diagnosis were identified, giving a prevalence of 241 per 100,000 (n=40; 95% confidence interval: 133-349 per 100,000). Many factors differed significantly between lupus cases and controls. Multivariate logistic regression analysis further identified previous and current smoking along with elevated serum levels of chloride, globulin, lactate dehydrogenase, uric acid, cholesterol, and lutein or zeaxanthin as risk factors; while protective factors against lupus included nonwhite race, obesity, elevated serum levels of bicarbonate, creatinine, total calcium, and vitamin B12, as well as elevated urinary albumin and iodine. Our nationwide data indicate that race, obesity, cigarette smoking, and certain biomarkers such as serum lutein or zeaxanthin, calcium, and cholesterol may be associated with the development or progression of lupus, although these findings need to be confirmed in further prospective investigations.